Community Synergy In Alternative Education Movements Through Home Schooling In The New Normal Era - Ana Lusiana; Mitri Sopiatun; Cici Fauziah; Ahmad Hamdan (Pancaran Pendidikan, 2021)
The current education process is hampered by the existence of the Covid-19 pandemic which requires education to be carried out online at home to cut the spread of the virus which will harm children, educators and education personnel. To anticipate this the need for community synergy to jointly find alternative movement solutions for education through home schools to optimize education in the new normal era. The purpose of this study was to determine the application of community synergy in the alternative movement of education through home schools. In the application process parents will not be burdened by the learning process of their children while at home because it will synergize with the teacher or tutor and also students as those who help in the application of the learning model of blended learning. The research method used is a descriptive qualitative approach. Data collection techniques through literature review / literature review. The results of this research are clearly seen how the community synergy will take place without walking between parents and teachers, because in essence education is our shared responsibility.